A generic geomorphological approach to archaeological interpretation and prospection in British river valleys : a guide for archaeologists investigating Holocene landscapes - Kohn, Marek
Landscape archaeology depends greatly on the nature of the underlying physical landscape, and an understanding of its formation processes and change. We are pleased to publish this contribution on the Holocene river valleys of Britain, which provides important guidance on the integration of archaeological and geomorphological evidence, in building models for assessing potential archaeological preservation and erosion.